Transgenic Expression of miR-133a in the Diabetic Akita Heart Prevents Cardiac Remodeling and Cardiomyopathy - Kambis, Tyler N.; Shahshahan, Hamid R.; Kar, Sumit; Yadav, Santosh K.; Mishra, Paras K. (Frontiers in Cardiovascular Medicine, 2019)
Advanced diabetes mellitus (DM) may have both insulin resistance and deficiency (double DM) that accelerates diabetic cardiomyopathy (DMCM), a cardiac muscle disorder. Reduced cardiac miR-133a, a cardioprotective miRNA, is associated with DMCM. However, it is unclear whether restoring miR-133a levels in the double DM heart could prevent DMCM. We hypothesized that increased cardiac levels of miR-133a could prevent DMCM in Akita, a mouse model of double DM. To test the hypothesis, we created Akita/miR-133aTg mice, a new strain of Akita where miR-133a is overexpressed in the heart, by crossbreeding male Akita with female cardiac-specific miR-133a transgenic mice. We validated Akita/miR-133aTg mice by genotyping and phenotyping (miR-133a levels in the heart). To determine whether miR-133a overexpression could prevent cardiac remodeling and cardiomyopathy, we evaluated cardiac fibrosis, hypertrophy, and dysfunction (P-V loop) in 13-14 week male WT, Akita, Akita/miR-133aTg and miR-133aTg mice. Our results revealed that miR-133a overexpression in the Akita heart prevents DM-induced cardiac fibrosis (reduced collagen deposition), hypertrophy (decreased beta-myosin heavy chain), and contractility (downregulated calcium handling protein sarco-endoplasmic reticulum-ATPase-2a). These results demonstrate that increased levels of miR-133a in DM heart could prevent cardiac remodeling. Our P-V loop analyses showed a trend of decreased cardiac output, stroke volume, and ± dp/dt in Akita, which were blunted in Akita/miR-133aTg heart. These findings suggest that 13-14 week Akita heart undergoes adverse remodeling towards cardiomyopathy, which is prevented by miR-133a overexpression. Thus, miR-133a could be a promising therapeutic candidate to prevent DMCM.